2020
DOI: 10.2196/17201
|View full text |Cite
|
Sign up to set email alerts
|

How Behavior Change Strategies are Used to Design Digital Interventions to Improve Medication Adherence and Blood Pressure Among Patients With Hypertension: Systematic Review

Abstract: Background Information on how behavior change strategies have been used to design digital interventions (DIs) to improve blood pressure (BP) control or medication adherence (MA) for patients with hypertension is currently limited. Objective Hypertension is a major modifiable risk factor for cardiovascular diseases and can be controlled with appropriate medication. Many interventions that target MA to improve BP are increasingly using modern digital tech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 106 publications
2
21
0
Order By: Relevance
“…A meta-analysis of 30 clinical trials uncovered that 5 mmHg reduction in SBP may lower the risk of cardiovascular events by 25-30% [31] In line with our finding, other Indonesian studies also demonstrated beneficial impact on BP improvement after provision of community pharmacist-directed health education through home visit [27,28,32,33]. Home care studies conducted overseas in USA [7,34], Canada [35], Australia [36] and less developed countries [17,29,37] also revealed similar findings on BP improvement.…”
Section: Resultssupporting
confidence: 85%
“…A meta-analysis of 30 clinical trials uncovered that 5 mmHg reduction in SBP may lower the risk of cardiovascular events by 25-30% [31] In line with our finding, other Indonesian studies also demonstrated beneficial impact on BP improvement after provision of community pharmacist-directed health education through home visit [27,28,32,33]. Home care studies conducted overseas in USA [7,34], Canada [35], Australia [36] and less developed countries [17,29,37] also revealed similar findings on BP improvement.…”
Section: Resultssupporting
confidence: 85%
“…There were opposing opinions regarding the gamification and social network components, also observed in a previous study with adolescents with asthma [ 20 ]. To accommodate these differences, and as personalized strategies to treatment adherence have better results [ 47 , 48 ], gamification and social network features of the app will become optional and patients not willing to use these features will be able to turn them off. This modification is in line with previous work advocating that flexible apps may better meet the needs of a broader range of patients [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, participants’ responses in interviews also revealed several concerns or limitations, suggesting that an app alone would not be a sufficient tool for self-management. Some external factors and barriers, for example, family, affected participants’ use of the app such as positively or negatively affecting patients’ optimism and self-esteem, or easing the stress of using the app to support the self-management of their disease [ 50 ]. These factors must also be considered when assessing the benefits of using apps to support the self-management of hypertension.…”
Section: Discussionmentioning
confidence: 99%